Study protocol: Exploratory trial of Forza™, an osmotin-based nutraceutical as adjuvant for the treatment of progressive multiple sclerosis - Viola Costa; Kenda Aluan; Irene Schiavetti; Caterina Bason; Tiziana Vigo; Elisa Leveraro; Corrado Cabona; Valeria Prada; Mauro Costagli; Vincenzo Daniele Boccia; Bruno Ruggiero; Giampaolo Brichetto; et al. (PLoS ONE, 2025)
Background Multiple Sclerosis (MS) is the first cause of non-traumatic neurological disability in young adults. Primary and secondary progressive MS are still lacking effective treatments. A new nutraceutical product made of lyophilised leaves of bioengineered kiwi plants (Actinidia deliciosa) overexpressing osmotin has recently been developed. Osmotin is a protein associated with stress adaptation in plant cells and it shares anti-inflammatory and neuroprotective properties with mammalian adiponectin. The aim of this study is to explore the safety and the efficacy of osmotin in progressive MS (PMS). Methods This is a prospective, multicenter, single-arm interventional, baseline vs treatment study that will be carried out by two Italian MS centers, where a total of fifty PMS patients will be recruited. Every patient will take a daily dosage of 5 grams of an osmotin-based nutraceutical, named Forza™ (9th Dimension Biotech, Inc.), for 6 months. Two pre-treatment assessments, at -6 months (-6M) and at baseline visit (M0), and two post-treatment assessments, at month 1 (M1), and at month 6 (M6) will be carried out. ForzaTM safety and activity, assessed by serum Neurofilaments Light (NfL) Chain quantification, are the primary outcomes of the study. Additional assessments will consist of clinical and neuropsychological evaluations, patient reported outcomes (PROs), brain magnetic resonance imaging (MRI), motor evoked potentials (MEPs) and optical coherence tomography (OCT). Discussion Disease modifying treatments in MS usually target inflammatory pathways with excellent results on reducing relapse associated disability but fail in preventing progression independent from relapse activity. This is a proof-of-concept study aimed at exploring the safety and the activity of an osmotin-based nutraceutical as an adjuvant treatment in PMS patients. Trial registration The trial was registered on July 10th 2023 at www.clinicaltrials.gov having identifier NCT05937802.